PELATIHAN PENCATATAN BARANG BERBASIS MICROSOFT EXCEL PADA TOKO SEMBAKO DESA CINTA KASIH - Dian Fiyonila; Mariskha. Z; Esya Alhadi; Raras Risia Yogasnumurti (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Business activities such as trading require systematic recording of buying and selling transactions. Grocery stores, which provide basic necessities, need accurate records of incoming and outgoing goods to monitor turnover and warehouse inventory, as well as to determine whether goods should be repurchased. Grocery stores vary in scale, ranging from small shops to larger enterprises. A store is considered large if its products are purchased not only by end consumers but also by wholesalers or retailers for resale. One of the larger grocery stores is Didi Grocery Store, located in Cinta Kasih Village, Gunung Megang District, Muara Enim Regency. As a partner in this service activity, the store faces several problems: (1) incoming goods are still recorded manually, (2) outgoing goods are not recorded, and (3) warehouse inventory is monitored only through direct physical checking before repurchasing goods. The implementation method in this activity involves processing data on incoming goods, outgoing goods, and inventory into an Excel-based recording system. Once the system is developed, training and application are provided for the partner. The results show that the activity successfully transformed the manual system of recording goods and inventory into a more effective and accurate Excel-based computer system.